Excitation and coupling of volume and surface fields on complex electrodynamic surfaces at mm‐wave and THz frequencies. Issue 11 (14th May 2020) - MacLachlan, Amy J.; Robertson, Craig W.; Cross, Adrian W.; Ronald, Kevin; Phelps, Alan D.R.
Abstract : The analytical theory describing the resonant excitation and coupling of volume and surface fields on the surface of two‐dimensional complex electrodynamic structures is presented. The theoretical analysis is valid over a broad frequency spectrum from mm‐wave frequencies through THz and even optical frequencies. An experimental study of planar periodic structures has been carried out using a vector network analyser calibrated to operate in the 140–220 GHz frequency range. Experimental results compare resonant eigenmode formation in two periodic surface lattice structures designed to operate within the 140–220 GHz frequency band; one periodic surface lattice etched onto a metal‐backed substrate and the other arranged to have an equivalent air separation. Dispersion diagrams derived from the analytical theory are presented. The results and theory are fundamental to some of the routes to the innovation of high‐power, mm‐wave and THz sources, solar cells, and novel sub‐wavelength absorbers.